The status of an isolated population of Goosander Mergus merganser in the Balkans - Catsadorakis, Giorgos; Avramoski, Oliver; Bojadzi, Andon; Bojadzi, Haris (Wildfowl, 2016)
This paper describes in detail for the first time the small, isolated population of Goosander Mergus merganser at the transboundary Prespa Lakes and Lake Ohrid in the Balkans. Co-ordinated censuses made during the breeding season each year from 2011–2015 inclusive estimated that there are 15–25 breeding pairs (15–34 according to the number of drakes counted) involving at least 77 individuals at Prespa Lakes, although numbers vary between years. The maximum number of young reared per pair in May–June 2011–2015 was estimated at 6.4 ± 3.5 (mean ± s.d., n = 35). During the period 1988–2013 the Prespa Lakes have also been the most important wintering site for this population, holding 4.8–100% (mean ± s.d.= 46.5 ± 29.5% ; n = 21) of the total numbers of Goosanders wintering in the southwest Balkans (i.e. in Albania, the FYR of Macedonia and Greece). Up to 130 birds overwinter in the region, where numbers have increased during the last 30 years, including at Prespa and Ohrid Lakes. The 2014 census provided first evidence of 3–4 pairs of Goosander nesting at Lake Ohrid, the second most important wintering site in the region. Conservation of this isolated population is of utmost importance, at least in a European context.